Fetal akinesia deformation sequence and massive perivillous fibrin deposition resulting in fetal death in six fetuses from one consanguineous couple, including literature review. Issue 11 (12th October 2021) - Tjon, Jill K.; Lakeman, Phillis; van Leeuwen, Elisabeth; Waisfisz, Quinten; Weiss, Marjan M.; Tan‐Sindhunata, Gita M. B.; Nikkels, Peter G. J.; van der Voorn, Patrick J. P.; Salomons, Gajja S.; Burchell, George L.; Linskens, Ingeborg H.; van der Knoop, Bloeme J.; et al.
Abstract: Background: Massive perivillous fibrin deposition (MPFD) is associated with adverse pregnancy outcomes and is mainly caused by maternal factors with limited involvement of fetal or genetic causes. We present one consanguineous couple with six fetuses developing Fetal Akinesia Deformation Sequence (FADS) and MPFD, with a possible underlying genetic cause. This prompted a literature review on prevalence of FADS and MPFD. Methods: Fetal ultrasound examination, motor assessment, genetic testing, postmortem examination, and placenta histology are presented (2009–2019). Literature was reviewed for the association between congenital anomalies and MPFD. Results: All six fetuses developed normally during the first trimester. Thereafter, growth restriction, persistent flexed position, abnormal motility, and contractures in 4/6, consistent with FADS occurred. All placentas showed histologically confirmed MPFD. Genetic analyses in the five available cases showed homozygosity for two variants of unknown significance in two genes, VARS1 (OMIM*192150) and ABCF1 (OMIM*603429). Both parents are heterozygous for these variants. From 63/1999 manuscripts, 403 fetal outcomes were mobilized. In 14/403 fetuses, congenital abnormalities in association with MPFD were seen of which two fetuses with contractures/FADS facial anomalies. Conclusion: The low prevalence of fetal contractures/FADS facial anomalies in association with MPFD in the literature review supports the possible fetal or genetic contribution causing FADS and MPFD in our family. This study with literature review supports the finding that fetal, fetoplacental, and/or genetic components may play a role in causing a part of MPFDs. Abstract : The low prevalence of fetal contractures/FADS facial anomalies in association with MPFD in the literature review supports the possible fetal or genetic contribution causing FADS and MPFD in our family. This study with literature review supports the finding that fetal, fetoplacental and/or genetic components may play a role in causing a part of MPFDs.